2002
DOI: 10.1046/j.1439-0396.2002.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a conjugated linoleic acid mixture on growth, organ weights, carcass traits and meat quality in growing pigs

Abstract: Grain soybean meal diets, either with 2% of a conjugated linoleic acid (CLA) preparation or with 2% rapeseed oil (control), were tested in 2 x 40 pigs, Pietrain x (Landrace x Large White), each group with 20 female in the live weight range 23.5-117.0 kg and 20 male-castrated pigs in the live weight range 23.5-110.6 kg. The CLA-content of the preparation amounted to 54.0% cis/trans + trans/cis, 8.7% cis/cis and 32.7% trans/trans isomers. Daily weight gain, feed intake and feed : gain ratio were not influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 18 publications
3
47
0
3
Order By: Relevance
“…Average BF, FAT and PFAT of castrates were significantly higher than those of gilts (29.01 vs. 25.56 mm, 9.57 vs. 7.55 kg and 21.79 vs. 17.43%, respectively). The results are in agreement with previous reports on sex differences (Larzul et al, 1997;Tischendorf et al, 2002;Cassady et al, 2004). However, Mohrmann et al (2006) did not find any significant differences between the sexes (gilts and barrows), but gilts tended to have higher lean meat content.…”
Section: Resultssupporting
confidence: 92%
“…Average BF, FAT and PFAT of castrates were significantly higher than those of gilts (29.01 vs. 25.56 mm, 9.57 vs. 7.55 kg and 21.79 vs. 17.43%, respectively). The results are in agreement with previous reports on sex differences (Larzul et al, 1997;Tischendorf et al, 2002;Cassady et al, 2004). However, Mohrmann et al (2006) did not find any significant differences between the sexes (gilts and barrows), but gilts tended to have higher lean meat content.…”
Section: Resultssupporting
confidence: 92%
“…13,21 In pigs, feeding 0.5% CLA containing 20% t10c12 and 27% c9t11 isomers reduced weight gain. 34 However, most pig studies have shown no change 16,35,36 or even increased weight gain 32,33 after supplementation with CLA mixture containing similar amounts of c9t11 and t10c12 isomers.…”
Section: Introductionmentioning
confidence: 99%
“…10,12,22,26 Studies that have not shown a significant reduction in weight gain generally are those having applied either low levels (r0.5% in the diet) of CLA 11,22 or CLA mixtures that contained low concentrations of the t10c12 isomer. 13,21 Results of the studies conducted in pigs are controversial, with an increase, 32,33 decrease 34 or no effect 16,35,36 being observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLA has been shown to have many biological effects for terrestrial animals, including remarkable inhibition of atherosclerosis (Lee et al, 1994), anti-cancer (Ha et al, 1990). In addition, there is increasing evidence that dietary CLA decreases body fat and increases lean body mass (Thiel-Cooper et al, 2001;Tischendorf et al, 2002), and thus attenuates obesity in several animal models (Delany and West, 2000;Wang and Jones, 2004). This has been suggested to be a positive effect in a variety of farmed species and animal disease models and by extension, humans (Thiel-Cooper et al, 2001;Wang and Jones, 2004).…”
Section: Introductionmentioning
confidence: 99%